MicroRNAs as predictive biomarkers of response to tyrosine kinase inhibitor therapy in metastatic renal cell carcinoma - Kovacova, Julia; Poprach, Alexandr; Buchler, Tomas; Cho, William C; Slaby, Ondrej (Clinical chemistry and laboratory medicine, 2018)
Renal cell carcinoma (RCC) accounts for 2%-3% of all malignant tumours. The first-choice treatment in metastatic RCC (mRCC) patients is tyrosine kinase inhibitors (TKIs). Although TKIs may prolong survival of the treated patients who are not primary resistant, almost all of them will eventually develop secondary resistance to the treatment after a progression-free period. To predict treatment response, thus, we need efficient biomarkers for rational indication of TKIs in mRCC. MicroRNAs (miRNAs) not only play important roles in the pathogenesis of many cancers, including RCC but also have been shown to serve as promising diagnostic, prognostic and predictive biomarkers in various cancers. However, the potential of miRNAs to predict response to therapy with TKIs in mRCC has not yet gained sufficient attention. Because personalisation of the TKIs indication in mRCC presents an important unmet medical need, we summarise research on this topic and give an overall insight on the current knowledge in this field.
Keywords: nádory ledvin; inhibitory angiogeneze; Humans; inhibitory proteinkinas; sunitinib; MicroRNAs; Biomarkers, Tumor; tyrosine kinase inhibitor; lidé; přežití bez známek nemoci; prediction; renal cell carcinoma; miRNAs; nádorové biomarkery; Protein Kinase Inhibitors; prognóza; Angiogenesis Inhibitors; karcinom z renálních buněk; Disease-Free Survival; Carcinoma, Renal Cell; mikro RNA; Sunitinib; Kidney Neoplasms; Prognosis